2014
DOI: 10.1038/jcbfm.2014.148
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Volumetric Changes Induced by Prolonged Hypoxic Exposure and Whole-Body Exercise

Abstract: The present study assessed the isolated and synergetic effects of hypoxic exposure and prolonged exercise on cerebral volume and subedema and symptoms of acute mountain sickness (AMS). Twelve healthy males performed three semirandomized blinded 11-hour sessions with (1) an inspiratory oxygen fraction (FiO 2 ) of 12% and 4-hour cycling, (2) FiO 2 = 21% and 4-hour cycling, and (3) FiO 2 = 8.5% to 12% at rest (matching arterial oxygen saturation measured during the first hypoxic session). Volumetric, apparent dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…However, a previous study only calculated a decrease in FA on DTI maps in patients with COPD (Zhang et al., 2012b). Furthermore, previous studies have reported contradictory results, showing either increased or reduced ADC values in hypoxic brains (Rowland et al., 2017; Rupp et al., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study only calculated a decrease in FA on DTI maps in patients with COPD (Zhang et al., 2012b). Furthermore, previous studies have reported contradictory results, showing either increased or reduced ADC values in hypoxic brains (Rowland et al., 2017; Rupp et al., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the structural and functional cerebral alterations to combined stressors (hypoxia + exercise) may make breathing stability during sleep an even greater challenge. Since measurable brain volume changes can occur in as little as 6‐h in hypoxia, it is not a surprise there would be significant, measurable differences in dependent variables (e.g. AHI) between‐group in the current study, especially after a concomitant exposure of 2 × 60‐min moderate‐intensity cycling plus 14‐h continuous hypoxic exposure.…”
Section: Discussionmentioning
confidence: 69%
“…Ventilatory responses to exercise in hypoxia, in awake individuals, significantly increases the ‘period’ of periodic breathing experienced, and are positively related to both cardiac output and the ventilatory response to CO 2. Further, Rupp and colleagues have found that prolonged, moderate‐intensity hypoxic exercise can accentuate the acute effects of hypoxia, significantly increasing total brain volume, by up to ∼2%. Thus, the structural and functional cerebral alterations to combined stressors (hypoxia + exercise) may make breathing stability during sleep an even greater challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, given that AMS symptom develops from several hours to 5 days following hypoxic exposure, AMS may contribute to cognitive impairment during prolonged exposure without acclimatization. Furthermore, exposure to hypoxia (hours to days) can lead to cerebral edema . Cerebral edema is the excess accumulation of fluid in the intracellular or extracellular regions of the brain, which is also known as brain swelling.…”
Section: Acute Exercise Severity and Duration Of Hypoxiamentioning
confidence: 99%